Potential influence of changes in tax benefits on charitable giving to higher education - Lee, Jin; Lee, Sungsil (Journal of Higher Education Policy and Management, 2024)
This study examined the impact of changes in tax codes on voluntary giving to universities and colleges. While higher education institutions have drawn attention to individual gifts and philanthropic donations as supplementary financial resources, the recent introduction of the Tax Cuts and Jobs Act of 2017 in the United States reduced tax incentives for charitable contributions, thus raising concerns regarding considerable declines in charitable giving. By using panel data from the Voluntary Support of Education Survey, this research revealed that changes in tax benefits on charitable giving as a consequence of the new tax policy are associated with an overall decrease in the sum of individual donations and the number of individual donors. This loss of voluntary contribution is notably observed in private colleges and universities with an emphasis on research activities.
Keywords: Charitable giving; donation; tax deduction; tax incentive; the tax cuts and jobs act of 2017